Determinants of consumers’ purchasing behaviours for rice in Rantau Panjang, Kelantan / Rj Muhamad Irham Rj Ismail - Rj Ismail, Rj Muhamad Irham (Faculty of Plantation and Agrotechnology, 2017)
Rice (Oryza sativa) is the most essential food crop which been cultivated worldwide. Rice production in Malaysia is low compared with other countries other rice growing in the world. This study is conducted at Rantau Panjang because the area is located near the Malaysia-Thailand border. The objectives of this study are to identify the purchasing behaviour of consumers on rice in terms of quality, to analyze the factors that affect consumer preferences on rice brands and to analyze the marketing factors of rice brand preferred by consumers. The methodology that has been implemented in this study is survey method. Based on the data, it showed that there is very strongly positive relationship between the acceptances of rice usually consumed by the consumer with the marketing factors of rice brands. The purchasing behavior of consumer on rice in term of quality and the consumer preferences on rice brands also have a strongly positive relationship with the acceptance of rice. From this study, it can be concluded that the marketing factors of rice is the most important because it can influence the acceptance of rice that the consumer preferred. For the recommendation, the supplier and seller of rice should study a lot about the marketing of rice to increase the sale of rice.